The Influence of Occupational Health and Safety (OHS) Training and Education on the Safety Awareness of Infrastructure Construction Workers in Muna Regency - Candra Kirana; Muhammad Suriyadarman Rianse (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
The high rate of occupational accidents in the construction sector is often attributed to low worker safety awareness. In regions like Muna Regency, where infrastructure development is intensifying, enhancing safety awareness through systematic Occupational Health and Safety (OHS) education and training is critical. However, empirical evidence on the effectiveness of such training in this specific regional context remains limited. This study aims to analyze the effect of OHS education and training on the safety awareness of infrastructure construction workers in Muna Regency. This research employed a quantitative approach with a survey method. Data were collected through structured questionnaires distributed to 100 construction workers selected via purposive sampling. The instruments measured variables related to OHS training and safety awareness using a Likert scale. Data analysis involved validity and reliability tests, followed by simple linear regression analysis using SPSS. The findings indicate that OHS education and training have a positive and significant effect on workers' safety awareness. The regression analysis resulted in a coefficient of determination (R²) of 0.42, meaning that 42% of the variance in safety awareness is explained by the training variable. The significance value was less than 0.05, confirming the statistical significance of this relationship. This study concludes that systematic OHS education and training are crucial factors in improving the safety awareness of construction workers in Muna Regency. These results highlight the need for contractors and local government agencies to prioritize and institutionalize continuous, high-quality OHS training programs to foster a stronger safety culture within the regional construction industry.